Prospect of PV Home system for Promoting and Stimulating Economic Development of Rural Bangladesh - Khan, M Fayyaz; Khan, M Mahmud (Journal of Electrical Engineering, 2011)
Poverty alleviation is the principle pre-condition for economic development of a developing country. In Bangladesh each village has about 355 households below the poverty line and the average income of these households is below Tk 3,500/-per month [1]. Rapid population growth and extreme scarcity of agricultural land require development of alternative sources of employment and income. Although the rural economy of Bangladesh is going through diversification, the pace of the progress can be significantly enhanced through human resource development and creation of alternative investment opportunities. In this paper, we argue that introduction of PV Home system could work as a catalyst in the process of transforming rural economy of Bangladesh. The PV Home system is likely to create opportunities home based income generating activities as well as better educational attainment for household members. Therefore, the PV Home system would have both short term and long term impacts on economic growth and diversification of rural economy. Index Terms: PV home system; rural households; annual flow; forward and backward linkage; solar radiation. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 39-42